Plunging ranula: surgical management of case series and the literature review - Olojede, Akanbi Clement Olurotimi (Clin Case Rep, 2017)
Plunging ranulas are rare; report of this condition is particularly limited in our environment. We present case series in children; with all cases having both oral and cervical components. It is important to note this type of presentation of plunging ranula and their appropriate management.